De abdij van Averbode: een verhaal van steen en marmer. - Ceukelaire, Marleen de (La pierre comme porteur de messages du chantier de construction et de la vie du bâtiment: actes du XXIe Colloque International de Glyptographie, Amay (Belgique), du 8 au 14 juillet 2018, 2019)
Keywords: averbode

De stichting van de Abdij van Averbode vanuit de bewaarde oorkonden (1133-1139) - Janssens, Herman (Premonstratenzers en premonstratenzerinnen in Brabant, 2019)
Keywords: averbode

De orgelgeschiedenis van de premonstratenzerabdij van Averbode ca. 1434-2001. Zes eeuwen orgelbouwkunst in Brabant. - Van Osta, J. (Katholieke Universiteit Leuven, 2019)
In the musicology of the Netherlands, the history of organ construction has its own place. For the Southern Netherlands, the organ history of the abbey of Averbode is particulary interesting. The size of the preserved old documents or the archive pieces go back to the fifteenth century. Other churches or abbeys also have valuable information, but it is often fragmented. Not only the size of the archives is important, but also the continuity. A chronological insight is given into a quasi-continuous organ history from the beginning of the fifteenth century until today. Information can be found about the late Gothic instrument, the Renaissance organ and its renovations to a Baroque organ and the new Rococo organ. After the period of the French Revolution, there is the transition from the classical to the romantic period. The building of the monumental romantic organ is a lasting reminder of this evolution. The present new Baroque organ illustrates the evolution of organ construction in the twentieth century. Both in older works and in more recent literature, the organ history of Averbode was the theme of several scientific publications. However, some of them restrict themselves to a fragmentary edition of archive pieces[1], or simply mention some instruments.[2] The sources are not further analysed or investigated within a broader organological context. Other researchers interpreted the sources from an obsolete and idealized romantic sound idiom. In that sense, there was almost no attention payed to the specific development of the organ type in the Southern Netherlands from the late Gothic to the Rococo period.[3] Yet other historians studied the individual instruments from the published archives, but they did not explain the link between the successive organs, their alterations and the evolution of the changing dispositions.[4] The present investigation wants to demonstrate that the publication of a synthesis of the organ history in Averbode — which has hitherto been lacking — is a valuable tool for the organological research of the Southern Netherlands and in particular of Brabant. The dissertation is structured chronologically. In addition to the discussion of the well-known and new archive pieces, the recent literature about organ building and organ builders working in Averbode, is critically discussed. The study begins with the earliest mentions of organs in the fifteenth and early sixteenth century. Subsequently the late Gothic instrument of Willem Boets van Heyst is discussed. The research focuses further on the activities of master Anthonis Toers and the specific developments of organ culture in the mid-sixteenth century. The organ of master Gielis Brebos of 1562 is a highlight of the sixteenth century organ history. The repairs, renovation, restoration and new construction by Martin Posselius, Jan Dillingen and Jan van Weert precede the in 1662 new built organ of Jan Dekens. Despite repairs and maintenance by various organ builders, the Jan Dekens organ is sold at the end of the eighteenth century. Averbode then asked Guillaume Robustelly to build a completely new instrument. Unfortunately, this remarkable instrument has only functioned during a short period. It is sold in the late days of the French time. After the reestablishment of the abbey in 1834, Arnold Graindorge builds a rather small instrument for the abbey church. However, this is replaced fairly quickly by a solid, romantic organ by Hippolyte Loret. This instrument has been preserved in an almost unspoilt state until today. However, it is waiting for a thorough restoration. In the quest for a new Baroque sound, Bernard Pels built a choir organ in 1979. As the Loret instrument became unplayable at the end of the twentieth century, the abbey chose to build a new transept organ by Léon III Verschueren in 2001. This Organ is the provisional endpoint of the rich organ history of the monastery of Averbode. In the second part of this study, all mentioned archives with regard to the instruments and their builders are published, with corrections where necessary. They are supplemented with other published transcriptions if they particularly concern the history of Averbode. Numerous newly discovered archive pieces of Averbode are published. They represent an important addition to what was already known, in particular concerning the design of the Renaissance organ (1530-1540), the difficulties in placing the Robustelly organ (1770-1773) and the ambiguities about the transitional instrument of Arnold Graindorge (1834-1844). The archives concerning the romantic instrument of Hippolyte Loret (1852-1859) have so far not been published. The construction history of the more recent instruments (1978, 1982 and 2001) are situated within the search for the authentic organ sound of mechanical organs with respect to the scientific research of ancient instruments. In supplementary annexes we offer a list of the main organists and composers connected to the abbey church of Averbode, the use of the organ in the premonstratensian liturgy, the relationship of Flor Peeters with the monastery of Averbode and the Organ Congresses which took place in the abbey. The registers on persons (organ builders), places, archives and authors want to be a service to the further critical examination of the organ culture in the Southern Netherlands. In this sense, this dissertation situates itself in the tradition of similar music historical monographs on the art of organ building in a particular church or location, or on a dynasty of organ builders that transcend local historiography[5]. [1] Norbertine and historian Placied Lefevre published in the years 1930 a lot of source material about the art history of Averbode with the fragmentary mentions of the organ history. P. Lefevre, Textes concernant l'histoire artistique de l'abbaye d'AverbodeIn Revue Belge d'Archéologie et d'Histoire de l'Art, 1935, 45-58. P. Lefevre, Textes concernant l'histoire artistique de l'abbaye d'Averbode aux Xviie Et XviiiE SièclesIn Revue Belge d'Archéologie et d'Histoire de l'Art, 1936, 151-176; 331-350 En 1937, 57-76. [2] E. Ganbat, Historique de la facture et des facteurs d'orgue avec la nomenclature des principales orgues placées dans les Pays-Bas et dans les provinces flamandes de la Belgique, suivi de la Galerie biographique d'organistes célèbres et d'une Notice sur les maître de Chapelle Et organistes de la cathédrale d'Anvers, Anvers, 1865, Avec une introduction et une nomenclature par Ghislain PotvliegHey, Frits Kaino, Amsterdam, 1972; J. Kreps, The Organ in The, Villagracia, 1933. [3] F. Van Der Mueren, Het orgel in de Nederlanden. Verre traditie - gebruik in de kerkelijke diensten - meubel - decoratieve houtversiering - orgelregistratie - orgelliteratuur - parallel-vergelijking tusschen al deze bestanddeelen, Leuven, 1931. [4] Jan (Trudo) Gerits (ex-confrater) published in the years 1960 and 1970 numerous articles on Averbodes organ history without however writing a monograph and clarifying the interconnections. [5] Good examples in Belgium and the Netherlands are: Persoons 1981; Lemmens 1985; van Nieuwkoop 1988; van Biezen 1995.
Keywords: averbode

“Copy destroyed”: de lotgevallen van een verdwenen incunabel - Popkema, Anne Tjerk; De Vries, Herre (De Gulden Passer, 2018)
[“Copy destroyed”: the fate of a missing incunabula]
Keywords: averbode

Brouwen van bier door de Abdij van Averbode - Janssens, Hans (Bier brouwen in Brabant tot aan de Franse tijd in het bijzonder in de norbertijinenabdijen, 2017)
Keywords: averbode

Voorwoord tot het Cartularium en Raadgevingen aan zijn Opvolgers voor het Bestuur van Abdij van Abt Arnold van Tuldel (prelaat van Averbode van 1368 tot 1394) - Exelmans, Eddy; Wouters, Jos (Mededelingenblad van de Heemkring Averbode, 2012)
Keywords: averbode

Liturgische handschriften met muzieknotatie in de premonstratenzer abdijen Grimbergen, Tongerlo, Park en Averbode: wat is voorhanden en welke zijn premonstratenzer handschriften? - Behrendt, Inga (Premonstratenzer gregoriaans in de Nederlanden : liturgische handschriften (13de-16de eeuw), 2011)
Keywords: averbode; grimbergen; park; tongerlo